New benzothiazinone linked 1, 2, 4-triazoles: Design, synthesis, characterization, and evaluation of antitubercular activity - Kannampally Ajmal, Gurubasavaraj V. Pujar, Sethu Arun Kumar, Subhankar P. Mandal, Manisha Singh (Journal of Applied Pharmaceutical Science, 2021)
Introduction: In a quest for developing active molecules to treat tuberculosis, we reported the design, synthesis, and antitubercular activity evaluation of benzo[1-4]thiazin-3(4H)-one encompassed 1-2-4-triazoles targeting the DprE1 (Decaprenylphosphoryl-beta-D-ribose oxidase) enzyme involved in cell wall component biosynthesis.Methodology: The antitubercular potential of the title compounds was screened against the standard strain of Mycobacterium tuberculosis H37Rv by Microplate Alamar Blue Assay (MABA) and in vitro cytotoxicity was screened against in human embryonic kidney 293 (HEK293T) cells. The prediction of ligand interactions to the target DprE1 enzyme’s binding site was realized through a molecular docking study.Results: Synthesized molecules have shown good antitubercular activity with reference to the standard antitubercular drugs. The 5c, 5e, and 6c are the most active antitubercular compounds having a minimum inhibitory concentration of 12.5 μg/ml. The synthesized molecules’ cytotoxic data reveal that tested compounds exhibited low in vitro cytotoxicity (higher IC50 values) in human embryonic kidney 293 (HEK293T) cells. Moreover, the prediction of ligand interactions to the target DprE1 enzyme’s binding site was realized through a molecular docking study. The compounds 6a-d have shown good docking scores, and their interactions with amino acids with active site pockets of the DprE1 were in line with the reference ligand.Conclusion: Thus, the adopted docking protocol is in good correlation to the in vitro antitubercular activity. Hence, benzo[1-4]thiazin-3(4H)-one encompassed 1-2-4-triazole scaffolds may provide the basis for developing new DprE1 inhibitors.
Keywords: 1-2-4-triazole, benzo[1-4]thiazin-3(4H)-one, MABA, Mycobacterium tuberculosis, MTT assay, DprE1 inhibitors.